The Benefit of Acronyms and Abbreviations in English and Arabic: An Analytical Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper shows the role of acronyms and abbreviations in communication across various domains, including education, business, government, and popular culture. It explores the origins, evolution, and functions of acronyms, elucidating their capacity to condense complex concepts, streamline communication, and foster community identity. Using a multidisciplinary approach drawn from linguistics, psychology and sociology, the study examines the cognitive processes involved in understanding acronyms and their impact on memory and decision-making. It also explores the problems posed by ambiguity, repetition and cultural context of acronyms and highlights the importance of context and clarity for clear communication. This is achieved by combining theoretical conclusions. Experimental data, where this article examines the impact of abbreviations on language and identity, in specific social and professional contexts, as well as in their practical application by the author examining the process of creating and using abbreviations, examining the mechanisms of their impact, as well as assessing how to strengthen internal and external relationships. In addition to the above, the study examined how acronyms are used in the political, marketing and branding fields, with a special focus on their ability to be easily remembered and attract attention. By analyzing the broader cultural and societal implications of acronym usage, this research contributes to a deeper understanding of language evolution, social cohesion, and communication strategies in the digital age.